2022
DOI: 10.1111/jsr.13744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total sleep deprivation on components of top‐down attentional control using a flexible attentional control task

Abstract: Summary Sleep deprivation consistently decreases vigilant attention, which can lead to difficulty in performing a variety of cognitive tasks. However, sleep‐deprived individuals may be able to compensate for degraded vigilant attention by means of top‐down attentional control. We employed a novel task to measure the degree to which individuals overcome impairments in vigilant attention by using top‐down attentional control, the Flexible Attentional Control Task (FACT). The FACT is a two‐choice task that has tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…We agree with this position, however we offer an addition to this approach which also takes into account the top-down influence of cortical neural networks, which likely also contributes to the overall picture of sleep related behavior ( 101 ). Previous research has shown that naturally, sleep deprivation or debt can lead to cognitive decline via top-down attention control deficits ( 102 ), while it has also been shown that sleep deprivation may not elicit deficiencies in bottom-up cognitive control ( 101 ). An apt metaphor is describing the contributions of both bottom-up and top-down influence over cognitive function as a balancing act .…”
Section: Discussionmentioning
confidence: 99%
“…We agree with this position, however we offer an addition to this approach which also takes into account the top-down influence of cortical neural networks, which likely also contributes to the overall picture of sleep related behavior ( 101 ). Previous research has shown that naturally, sleep deprivation or debt can lead to cognitive decline via top-down attention control deficits ( 102 ), while it has also been shown that sleep deprivation may not elicit deficiencies in bottom-up cognitive control ( 101 ). An apt metaphor is describing the contributions of both bottom-up and top-down influence over cognitive function as a balancing act .…”
Section: Discussionmentioning
confidence: 99%
“…Although the harmful effects of TSD on individual cognitive function have been confirmed in numerous studies, some have found that different durations of sleep deprivation may have different effects on individual cognitive function [ 32 ]. At the behavioral level, Stenson (2023) [ 33 ] subjected 12 adults to 36 h of TSD and found that attentional functioning tended to decline between 20 and 36 h of TSD. Skurvydas (2021) [ 32 ] showed no significant change in reaction time to complete the Go/No-Go task after 24 h of TSD in 19 healthy adult males, but a significant increase in reaction time to the Go/No-Go task after 48 h of TSD (48 h TSD).…”
Section: Introductionmentioning
confidence: 99%